2021
DOI: 10.1002/cti2.1350
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cells are not productively infected by SARS‐CoV‐2

Abstract: ObjectivesThrombotic and microvascular complications are frequently seen in deceased COVID‐19 patients. However, whether this is caused by direct viral infection of the endothelium or inflammation‐induced endothelial activation remains highly contentious.MethodsHere, we use patient autopsy samples, primary human endothelial cells and an in vitro model of the pulmonary epithelial–endothelial cell barrier.ResultsWe show that primary human endothelial cells express very low levels of the SARS‐CoV‐2 receptor ACE2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
95
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(115 citation statements)
references
References 76 publications
8
95
2
2
Order By: Relevance
“…Nonetheless, the extent to which the direct infection of endothelial cells by SARS-CoV-2 contributes to vascular involvement in COVID-19 remains to be determined and may indeed be organ and tissue dependent. In vitro cultures of primary human umbilical vein endothelial cells (HUVECs) and human microvascular endothelial cells from the lung (HMVEC-L) did not support SARS-CoV-2 infection [157]. These HUVECs and HMVES-L cells expressed very low levels of ACE2 and TMPRSS2 and did not show any morphological changes upon virus exposure to their apical or basal surface.…”
Section: Vasculaturementioning
confidence: 96%
“…Nonetheless, the extent to which the direct infection of endothelial cells by SARS-CoV-2 contributes to vascular involvement in COVID-19 remains to be determined and may indeed be organ and tissue dependent. In vitro cultures of primary human umbilical vein endothelial cells (HUVECs) and human microvascular endothelial cells from the lung (HMVEC-L) did not support SARS-CoV-2 infection [157]. These HUVECs and HMVES-L cells expressed very low levels of ACE2 and TMPRSS2 and did not show any morphological changes upon virus exposure to their apical or basal surface.…”
Section: Vasculaturementioning
confidence: 96%
“…For instance, transwell filter systems allow for initiation of the viral infection via different compartments, namely apical and basolateral. The study of Schimmel et al (2021) showed that the virus cannot actively replicate in umbilical cord and microvascular endothelial cells, but SARS-CoV-2 is able to enter the cell via either the apical or basolateral side ( Schimmel et al, 2021 ). Moreover, a pro-inflammatory response of the cells was observed, indicative of an interaction of the virus with the cells.…”
Section: Covid-19 and Vascular Cellsmentioning
confidence: 99%
“…In addition, the endothelial cells are exposed to shear stress in vivo , and therefore employing microfluidic devices is a potentially interesting technique mimicking the natural vascular environment. Endothelial cells that were seeded in a polydimethylsiloxane (PDMS) channel containing a collagen hydrogel were infected under flow, but also this method did not allow for viral replication of SARS-CoV-2 in the endothelial cells ( Schimmel et al, 2021 ). This is an interesting finding since it has been described that shear stress could upregulate ACE2 expression in brain microvascular endothelial cells, thereby allowing for attachment of the S protein, as shown in ( Kaneko et al, 2021 ) Figure 3 .…”
Section: Covid-19 and Vascular Cellsmentioning
confidence: 99%
“…S3a). SARS-CoV-2 is able to infect human blood vessel organoids and ECs in vitro without undergoing viral replication and induces a clear proinflammatory response [ 17 ]. Therefore, we were able to demonstrate that in ECs, ERK1/2 activity in response to 40 ng/ml RBD increased gradually up to ~ 30% after 24 h (Fig.…”
Section: Resultsmentioning
confidence: 99%